Analysis on the socio-cultural values of the traditional Malay houses compound - Ibrahim, Illyani; Roslee, Noranisa; Abdullah, Alias; N Murtaza, Fatin Farhana (Malaysian Institute Of Planners, 2020)
The Malay traditional environment is the interaction between human, natural environment, and culture, which is then translated into the spatial design of houses and their surroundings. However, rapid urbanisation has transformed many traditional villages by incorporating urban elements into the villages. This study focuses on understanding the existence of the socio-cultural values of a traditional Malay house compound in Kampung Paya Rumput Jaya, Melaka. The objective of this study is to identify the Malay socio-cultural values and the spatial arrangement of the traditional Malay house compound. Data were collected by means of a questionnaire survey, semi-structured interviews, a mapping analysis (site inventory), and a thematic/content analysis (interviews). The findings indicate that the community in the villages are still upholding the Malay traditional socio-cultural values. Future design of a house compound should incorporate the characterisation of a traditional Malay houses compound for maintaining at least part of the Malay traditional socio-cultural values.